APLICAÇÃO DE MÉTODOS GEOFÍSICOS NO ESTUDO DO AQUÍFERO TACARATU NA REGIÃO DE BUÍQUE, PERNAMBUCO - Oliveira, Roberto Gusmão de; Galvão, Manoel Júlio da Trindade Gomes; Freire, Almir Gomes (Águas Subterrâneas, 2001)
Resumo não disponível.